Implementation of an ARM7 dual-core microprocessor using Xilinx Spartan-IIE Family of FPGA - Busok, Gino Jr. C.; Choi, Daniel Saihung Lui.; Elpa, Neil Xavier C. (2007)
The current trend of microprocessor technology is to increase the number of processing cores in a single chip instead of increasing the clock speed. These multi-core microprocessors allow parallel processing which decreases processing time as well as heat and power consumption. Concurrently, the number of electronic design applications using Field Programmable Gate Array (FPGA) devices is growing. The use of FPGA has become a fast and inexpensive way of implementing and testing a hardware electronic design. The purpose of this project is to combine these two popular technologies. The project started with modifications of the base ARM7 microprocessor into a dual core processor and implements it in an FPGA device. The two cores share a single bus and a single memory and they have no cache. The codes are written in Very High Speed Integrated Circuit Hardware Definition Language (VHDL) and the target FPGA device is the Xilinx Spartan-IIE XC2S600E. The FPGA board with the downloaded dual-core ARM7 microprocessor was tested using logic analyzer. The test benches include instruction mixes for single core ARM7 microprocessor, multiply instruction and atomic instructions, namely Compare-and-Swap, Test-and-Set and Fetch-and-Add. It was also found out that the minimum clock period for the design to function properly is 250 ns. The final area utilization for the design is 88% for the slices available, 53% of available LUTs was occupied and 32% IOB was used.
Thesis (B.S. CoE)--University of the Philippines Diliman.
Keywords: Microprocessors -- Design and construction; Field programmable gate arrays -- Design and construction; Xilinx Spartan; ARM7 microprocessor